Effect of papain enzyme supplementation on growth performance and nutrient utilization of catfish (Pangasius hypopthalmus) - Diana Rachmawati; Prihanto, Asep A. (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to evaluate the effect of papain enzyme diet on growth performance of Catfish (Pangasius hypopthalmus) through feed efficiency and growth parameters. The research employed a completely randomised design with four treatments and three replicates. Catfish fingerlings with an average weight of 2.23 g/fish were used as samples. The experimental diets were prepared to be isonitrogenous (31%) and isocaloric (252.06 kcal/g). Papain enzyme was added to the feed within various doses; A (0 g/kg feed), B (2 g/kg feed), C (4 g/kg feed), D (6 g/kg feed) and E (8 g/kg feed). The study parameters included apparent digestibility coefficient of protein (ADCP), relative growth rate (RGR), the efficiency of feed utilisation (EFU), feed conversion ratio (FCR), protein efficiency ratio (PER), survival rate (SR) and water quality. The results of the study show that the addition of papain enzyme significantly affected ADCp, RGR, EFU, FCR, and PER, but not the SR of catfish. Based on regression analysis, the optimum dose of ADCP and RGR were 4.05 g/kg, RGR was 4 g/kg feed, respectively. The EFU had an optimum dose of 3.93 g/kg feed, meantime the FCR and PER had an optimum dose of 4 g/kg feed each. In conclusion, the diet of papain in the amount of 4 g/kg feed increased the growth performance and nutrient utilisation of catfish (Pangasius hypopthalmus).